Behavioural individuality in clonal fish arises despite near-identical rearing conditions - David Bierbach (Nature Portfolio, 2017)
Genetically-identical animals experiencing the same environmental conditions should develop, in theory, identical behavioral traits. However, Bierbachet al. show here that behavioral differences still emerge among cloned fish under tightly controlled experimental conditions.